Building Information - Representation and Management Fundamentals and Principles - Koutamanis, Alexander; Open Textbook Library (Open Textbook Library, 2019)
The book presents a coherent theory of building information, focusing on its representation and management in the digital era. It addresses issues such as the information explosion and the structure of analogue building representations to propose a parsimonious approach to the deployment and utilization of symbolic digital technologies like BIM.
Part I. Digitization -- 1. Digital information -- Part II. Building representation -- 2. Representation -- 3. Analogue respresentations -- 4. Building representations in BIM -- Part III. Information: theory and management -- 5. Data and information -- 6. Information management -- 7. Process and information -- Part IV. Exercises -- Key concepts -- Exercise I: maintenance -- Exercise II: change management -- Exercise III: circular energy transition
In English.
Description based on print resource
Keywords: Engineering -- Textbooks; Civil -- Textbooks